2003
DOI: 10.1101/gr.1113003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative DNA Sequence Analysis of Wheat and Rice Genomes

Abstract: The use of DNA sequence-based comparative genomics for evolutionary studies and for transferring information from model species to crop species has revolutionized molecular genetics and crop improvement strategies. This study compared 4485 expressed sequence tags (ESTs) that were physically mapped in wheat chromosome bins, to the public rice genome sequence data from 2251 ordered BAC/PAC clones using BLAST. A rice genome view of homologous wheat genome locations based on comparative sequence analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Here we report an ordered and annotated assembly (IWGSC RefSeq v1.0) of the 21 chromosomes of the allohexaploid wheat cultivar CS, an achievement that is built on a rich history of chromosome studies in wheat (10)(11)(12), which allowed the integration of genetic and genomic resources. The completeness and accuracy of IWGSC RefSeq v1.0 provide insights into global genome composition and enable the construction of complex gene coexpression networks to identify central regulators in critical pathways, such as flowering-time control.…”
mentioning
confidence: 99%
“…Here we report an ordered and annotated assembly (IWGSC RefSeq v1.0) of the 21 chromosomes of the allohexaploid wheat cultivar CS, an achievement that is built on a rich history of chromosome studies in wheat (10)(11)(12), which allowed the integration of genetic and genomic resources. The completeness and accuracy of IWGSC RefSeq v1.0 provide insights into global genome composition and enable the construction of complex gene coexpression networks to identify central regulators in critical pathways, such as flowering-time control.…”
mentioning
confidence: 99%
“…In the present study, we also observed that no RuvbL gene was present on homoeologous chromosomes of rice and wheat, suggesting their diverse evolution. For example, TaRuvBL1a genes are present on each of the three chromosomes of homoeologous group 4 (4A, 4B, and 4D); these three genes are orthologues of the rice gene OsRuvBL1a located on rice chromosome 1, which is not homoeologous to chromosome of homoeologous group 4 of wheat (Ahn et al 1993;Sorrells et al 2003). Similarly, RuvBL1b genes are located on 3A, 3B, 3D chromosomes of wheat and an unrelated rice chromosome 7.…”
Section: Taruvbl Genes In Wheat and Related Speciesmentioning
confidence: 99%
“…To date, studies have identified more candidate genes and generated more breeding applications related to NUE in rice than in wheat [ 22 , 54 ] ( Table 2 ). Translating insights from rice to wheat require herculean efforts, largely because of differences in genomic size and structure [ 22 , 144 , 145 ]. New mutant resources [ 146 ] and transgenic tools [ 147 ], however, increase the feasibility of characterizing candidate genes across a polyploid genome.…”
Section: Puzzles—knowledge Gaps About Modifying Nitrogen Metabolism F...mentioning
confidence: 99%